MANAJEMEN PENDIDIKAN SEKS PADA ANAK PENYANDANG TUNAGRAHITA - farid Setiawan (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
Sexual violence or sexual harassment has always been a problem that never stops, every year it always increases. Sexual violence can happen to anyone, including children with mental retardation. Children with mental disabilities are those with mental retardation, where their mental condition is below normal limits, this condition is also known as mental retardation, but physically they are normal. It is appropriate to educate them about sexual education, because after all they have to be independent and be able to stand on their own feet. So it takes a proper management management in delivering sexual education to them. Based on the results of the research, it was found that educational management was learning about gender differences and the cultivation of character education. The learning model that can be applied is the center learning model, with the concept of role playing. This is what will be discussed in this article in order to alleviate children with mental retardation from violence or sexual harassment that threatens their future.